Avaliação da qualidade de vida dos pacientes submetidos a artroplastia total primária do quadril antes e após a cirurgia - Lima, Aparecida Bezerra de [UNESP] (2015)
Among the chronic-degenerative diseases (DNC) that affect the elderly's quality of life, we can highlight the degenerative joint diseases, among them the osteoarthritis (OA) of the hip that affects 33.6% of the population in an average age of 65 years or more, with impact on the quality of life. Objective: It is to evaluate the quality of life of the patients who are undergoing Primary Total Hip Arthroplasty (ATQP) due to osteoarthritis before and after six months of surgery, moreover the impact of the waiting time for the surgery in the quality of life and functional and physical aspects. Method: We evaluated 39 patients at the Outpatient Clinic of Specialties Governor Mario Covas of the Medicine College of Marilia. Have taken part of the study all the patients that were submitted to ATPQ in the period of December 2011 to June 2013. Data were collected regarding the socio-demographic characteristics; quality of life related to health (The Medical Outcomes Study-36 item Short-Form Health Survey (SF-36); evaluation questionnaire of a functional evaluation of the hip Harris Hip Score (HHS); and instrument Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). The data collection happened in two moments: preoperative (before surgery) and in the postoperative period, six months after the surgery. Have been made a description of variables collected and later statistical analysis of the data in the different areas of the instruments applied comparing the pre and postoperative moments and the waiting time for surgery (< ou >than 18 months) using the student's t test paired. Results: the patients had a mean age of 62.9 + 9.5 years, and 64.1% were male. The comparison of preoperative and postoperative identified: an improvement in the evaluation of the quality of life related to health- the SF-36 in all dimensions (p < 0.05), functional capacity ; the HHS the total score and subscales: pain, Activities of Daily Living, gait ...